2006
DOI: 10.1590/s0103-97332006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Improved electronic structure and optical properties of sp-hybridized semiconductors using LDA+U SIC

Abstract: We propose the local density approximation (LDA) plus an on-site Coulomb self-interaction-like correction (SIC) potential for describing sp-hybridized bonds in semiconductors and insulators. We motivate the present LDA+U SIC scheme by comparing the exact exchange (EXX) hole with the LDA exchange hole. The LDA+U SIC method yields good band-gap energies E g and dielectric constants ε(ω≈ 0) of Si, Ge, GaAs, and ZnSe. We also show that LDA consistently underestimates the Γ-point effective electron m c and light-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 9 publications
2
55
0
Order By: Relevance
“…However, the effective electron masses at the CBM are relatively small for these compounds, for instance: m x ≈ 0. [23,24]). Interestingly, two of the mass components (m x and m z ) are similar for the two compounds, while the third compound (i.e., m y ) is significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effective electron masses at the CBM are relatively small for these compounds, for instance: m x ≈ 0. [23,24]). Interestingly, two of the mass components (m x and m z ) are similar for the two compounds, while the third compound (i.e., m y ) is significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…A large k-mesh can be important to describe details in the absorption coefficient [21,22]. However, from test calculations we have found that the effect is not crucial for the considered materials, and we use HSE06 (which avoids incorrect resonance across the underestimated gaps for local potentials [23,24]) and with the same k-mesh as for the calculations of the LDOS.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the band-gap energy of both CIS and CGS can be obtained from the similar SIC within LDA+U SIC . We have found [6] that effective masses and optical properties are somewhat overcompensated by fitting the LDA+U SIC band-gap energy to the exact experimental value. This can be a side effect of the energy-independent LDA+U SIC approach, but it can also be an indication that one may not be able to extract the experimental band-gap energy from the single-particle DFT/Kohn-Sham eigenvalues.…”
Section: Electronic Structurementioning
confidence: 97%
“…LDA fails to accurately describe this valence d-state localization in ZnO [9], where the LDA cation-anion 3d2p-hybridization disagrees with soft x-ray emission spectra. This shortcoming was corrected by the LDA+U SIC approach [6,9]:…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation